Negotiating Tradition and Islamic Norms: Muhammadiyah Leaders’ Perspectives on Caci Dance in Wedding Rituals through the Lens of ‘Urf in West Manggarai - Ilham Maulana (Journal of Family and Sharia, 2026)
The interaction between Islamic reformist movements and local cultural traditions remains a complex and contested issue in contemporary Muslim societies. This study examines how Muhammadiyah leaders interpret and respond to the Caci dance tradition performed in wedding rituals in West Manggarai, Indonesia, through the lens of ‘urf (customary practice) in Islamic law. While Muhammadiyah is often associated with a purifying approach to religion, local realities frequently require negotiation between doctrinal norms and deeply rooted cultural expressions. This research adopts a qualitative case-oriented approach, drawing on in-depth interviews, document analysis, and socio-religious observations to explore the perspectives of Muhammadiyah leaders in Tiwu Nampar Village. The analysis focuses on how ‘urf is utilized as a conceptual framework to assess the legitimacy of the Caci dance within Islamic teachings. The findings reveal a spectrum of views, ranging from rejection based on concerns over elements perceived as inconsistent with Islamic values, to conditional acceptance that emphasizes cultural preservation as long as it does not violate core religious principles. Furthermore, the study demonstrates that ‘urf serves as a mediating tool that allows for contextual interpretation of Islamic norms in relation to local traditions. Muhammadiyah leaders engage in a process of negotiation that reflects both their commitment to religious reform and their awareness of social cohesion within the community. This negotiation highlights the dynamic nature of Islamic law, where cultural practices are neither wholly accepted nor rejected, but critically evaluated based on their alignment with ethical and religious objectives. The study contributes to broader discussions on Islamic reformism, legal pluralism, and the accommodation of local culture within Islamic jurisprudence. It argues that understanding the role of ‘urf is essential for bridging the gap between normative Islamic teachings and lived cultural realities. Ultimately, this research underscores the importance of contextual and dialogical approaches in addressing tensions between tradition and religious norms in contemporary Muslim communities.